UNIVERSITY GOVERNANCE AND LEADERSHIP IN KENYA - Amukowa, Wycliffe (Center for International Research Development, 2021)
Governance in university education is said to involve the powers to make decisions about fundamental policies and practices in several critical areas concerning universities such as mission, enrolment size, the access of students to instructional programmes and the access of citizens to other services, degree requirements, and freedom available to individual faculty members among other domains. This paper discusses how governance of universities in Kenya is conducted and further highlights leadership qualities that a vice-chancellor, who is the chief executive officer of a university needs in order to govern.
Keywords: Charter; Governance; Leadership; Statutes; University; Vice-Chancellor